Implementation of Pulmonary TB Management Program with Pulmonary Tuberculosis Patient Treatment Monitoring Information System (SISFOTBPARU) - Sri Indra Trigunarso; Zainal Muslim; Amrul Hasan (Poltekkes Kemenkes Tanjung Karang, 2024)
Various factors are thought to hinder the success of TB treatment, including failure of therapy due to non-compliance as one of the main factors. The solution is expected to be the development of an android-based pulmonary tuberculosis patient treatment monitoring information system application (SISFOTBPARU). This study aims to assist the operational health officers of the Kampung Sawah, Satellite, and Kedaton Bandar Lampung Health Centers in monitoring the treatment of TB patients at their Health Centers. Based on the results of the black box testing that had been carried out, the application could run according to the development design. In the UAT test using a list of questions for each application user using Likert's summed rating scaling calculation technique, for users of Kampung Sawah, Satellite, and Kedaton Health Center Officers in Bandar Lampung, 76.0% of users stated that it was very appropriate and 24.0% stated that it was proper that the menus displayed on the application met the expectations of health center officers. In the Testing of the Application for Patient Users of Kampung Sawah, Satellite, and Kedaton Health Centers in Bandar Lampung, 78.7% of users stated that it was very appropriate, and 21.3% stated that it was proper that the menus displayed on the application made it easier for patients to report their treatment activities. This study proves that the criteria for success include the web and Android TB patient treatment monitoring applications used by health workers at Kampung Sawah, Satellite, and Kedaton Health Centers and TB patients.